Lived Experiences of Differently Abled Students: A Basis for University-Based Health Programs - Francheska Mae O. Antonio; Jan Christian T. Aquino; Joshua Dave S. Aquino; Cristel Xyrene A. Barayuga; Gerianne M. Beley; Jaramae M. Cabacungan; Gil Fabien S. Cabrera; Abigail M. Cajuigan; June Christian G. Reguyal (UM Purwokerto Press, 2025)
Background: In the Philippines, students with disabilities continue to face challenges in higher education, including limited accessibility, lack of initiatives, and insufficient health support. These issues affect not only their academic performance but also their overall well-being. While national laws advocate for disability inclusion, there remains a limited body of localized research exploring the lived experiences of differently-abled students in university settings, particularly regarding their health-related needs and accessibility to student services. This study aimed to examine the lived experiences of differently-abled students at the Nueva Ecija University of Science and Technology (NEUST) and use their insights as a basis for developing university-based health programs tailored to their specific needs. Method: The researchers used a qualitative phenomenological approach, involving semi-structured interviews with eleven (11) differently-abled students across two (2) NEUST campuses. Through purposive sampling, participants were selected, and data were analysed using thematic analysis to extract recurring patterns and core experiences. Results: Five major themes emerged, including Health Behind the Hallways, Learning through Limits, Belonging Matters, Voices from the Journey towards Campus Readiness, and Building Better Spaces. Conclusion: The findings highlight opportunities for the Nueva Ecija University of Science and Technology (NEUST) to consider enhancing health services, improving campus accessibility, and establishing more inclusive support systems to create a more conducive learning environment for differently abled students. These efforts are crucial for creating equitable educational environments where all students, regardless of their abilities, can thrive.